Chemovirotherapy of Lung Squamous Cell Carcinoma by Combining Oncolytic Adenovirus With Gemcitabine - Liu, Xing; Yang, Zhiguang; Li, Yiquan; Zhu, Yilong; Li, Wenjie; Li, Shanzhi; Wang, Jing; Cui, Yingli; Shang, Chao; Liu, Zirui; Song, Gaojie; Li, Ce; et al. (Frontiers in Oncology, 2020)
Oncolytic virotherapy is emerging as an important agent in cancer treatment. In a previous study, we designed and constructed Ad-Apoptin-hTERTp-E1a (Ad-VT), a dual cancer-selective anti-tumor recombinant adenovirus. In this study, crystal violet staining and WST-1 assays showed that Ad-VT has a significant tumor killing effect in a time and dose dependent manner. The combination of Ad-VT (10 MOI) and gemcitabine (10 nM) significantly inhibited NCI-H226 cells, but did not increase the killing effect of gemcitabine on human normal bronchial epithelial cells BEAS-2B. Hoechst, JC-1 and Annexin V experiments demonstrated that the combination of Ad-VT and gemcitabine mainly inhibited NCI-H226 cell proliferation by inducing apoptosis (mitochondrial pathway). The combination also significantly inhibited the migration and invasion abilities of NCI-H226 cells. In vivo, Ad-VT in combination with low-dose gemcitabine could effectively inhibit tumor growth and prolong survival of mice. Ad-VT has the characteristics of tumor-selective replication and killing, in vitro and in vivo. The combined application of Ad-VT and gemcitabine has a synergistic effect, which can increase the anti-tumor effect and reduce the toxicity of chemotherapy drugs, indicating that Ad-VT has a potential clinical value in the treatment of lung squamous cell carcinoma.